2015
DOI: 10.1167/iovs.15-16610
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Fibroblasts From Graves' Orbitopathy Patients Share Functional and Immunophenotypic Properties With Mesenchymal Stem/Stromal Cells

Abstract: The in vitro data obtained in this study provide the first experimental evidence that orbital fibroblasts derived from retrobulbar fat of GO patients share biological characteristics with MSCs. These findings provide new insight into the biology of key cells in GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
(56 reference statements)
0
14
0
1
Order By: Relevance
“…OFs from GO patients have also been characterized [2830]. Several studies have provided experimental evidence that OFs derived from retrobulbar fat of GO patients have similar immunophenotypic features and differentiation abilities as MSCs but differ in terms of their immunosuppressive potential [28, 29]. Furthermore, comparative analyses of adipose-derived MSCs from GO orbital fat and abdominal fat have been conducted to understand the phenotypic characteristics of OFs in GO patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…OFs from GO patients have also been characterized [2830]. Several studies have provided experimental evidence that OFs derived from retrobulbar fat of GO patients have similar immunophenotypic features and differentiation abilities as MSCs but differ in terms of their immunosuppressive potential [28, 29]. Furthermore, comparative analyses of adipose-derived MSCs from GO orbital fat and abdominal fat have been conducted to understand the phenotypic characteristics of OFs in GO patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis by flow cytometry has shown that orbital fibroblasts are largely positive for CD90 (Thy-1) and negative for CD45 85,86 (Figure 2). There is potential for strategies that use the suppressive function of regulatory T cells to also prove beneficial to patients with Graves' orbitopathy 91 .…”
Section: [H2] Rituximabmentioning
confidence: 99%
“…While these studies suggested potential site-specific differences between fibroblasts, direct comparison of fibroblasts derived from different adipose tissue depots of the same donors has not been reported. On the other hand, Brandau et al 15 demonstrated comparable immunophenotypic and multipotent properties yet distinct functional differences between orbital fibroblasts derived from explant culture and ADSC generated by enzymatic digestion using the same aliquot of orbital adipose tissues from patients with TAO. Whether ADSC from patients with TAO demonstrates such site-specific features is not known.…”
Section: Discussionmentioning
confidence: 99%